Management and Entrepreneurship Assistance for Rural Pig Farming Group in Bali - Sitiari, Ni Wayan; Ekayani, Ni Nengah Seri; Ariana, I Nyoman Tirta (Asian Journal of Community Services, 2024)
The Community Partnership Program aimed to enhance pig farmers' swine breeding management skills and entrepreneurial orientation in Manikyang village, Bali. Through counseling and mentoring, farmers improved their knowledge of piglet selection, feed composition, and pen layout. The program also introduced online marketing strategies and basic book-keeping. Farmers displayed high enthusiasm and began to see pig farming as a profitable business. Initial challenges included misunderstandings of optimal farming practices and a lack of entrepreneurial mindset and systematic book-keeping. Despite these obstacles, the program achieved significant improvements. Farmers now understand the importance of proper management and entrepreneurial practices. However, ongoing support is essential to further enhance the farmers' risk-taking abilities and sustain progress, ensuring long-term success and development.